Desain Didaktis Materi Eksponensial Untuk Mengatasi Learning Obstacle Pada Siswa Kelas X SMA - Sania, Titi; Fuadiah, Nyiayu Fahriza; Sari, Eka Fitri Puspa (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to design a didactic design for learning exponential material to overcome students’ learning obstacles and design a hypothetical learning trajectory. This research is a Didactical Design Research study which has three stages of analysis, namely prospective analysis, method didactic analysis and retrospective analysis. The results of this research show the learning obstacles experienced by students in exponential material, students experience difficulty in solving conceptual, procedural and contextual problems because students do not understand the prerequisite material first. HLT is structured based on the LO experienced by students, namely 1) difficulty in determining formulas for the properties of exponential number operations; 2) difficulty in simplifying questions about the properties of exponent numbers; 3) difficulty in solving contextual problems in exponential material. From the didactic design, the diagnostic test was implemented so that the results of the final identification test were obtained, namely that there was a decrease in LO experienced by students, namely 1) calculating one of the exponentials (conceptual) properties from 25% to 15%; 2) calculate about exponential (procedural) properties from 35% to 0%; 3) solving problems systematically regarding problems related to exponential properties from 50% to 35%.